Queer Blake
XI, 264 p.
Keywords: Numerous claims have been made for a sexual Blake, from post-lapsarian pessimist to free-loving hippie. Queer Blake raises a flag for the weird, perverse, camp and gay directions of the artist's life and work. The contributors occupy diverse positions, illustrating what fresh interpretations result when heterosexuality is ditched as an ideal.